A structure‐function approach to optimizing TLR4 ligands for human vaccines. Issue 11 (2nd November 2016) - Carter, Darrick; Fox, Christopher B; Day, Tracey A; Guderian, Jeffrey A; Liang, Hong; Rolf, Tom; Vergara, Julie; Sagawa, Zachary K; Ireton, Greg; Orr, Mark T; Desbien, Anthony; Duthie, Malcolm S; et al.
Abstract : Adjuvants are combined with vaccine antigens to enhance and modify immune responses, and have historically been primarily crude, undefined entities. Introducing toll‐like receptor (TLR) ligands has led to a new generation of adjuvants, with TLR4 ligands being the most extensively used in human vaccines. The TLR4 crystal structures demonstrate extensive contact with their ligands and provide clues as to how they discriminate a broad array of molecules and activate or attenuate innate, as well as adaptive, responses resulting from these interactions. Leveraging this discerning ability, we made subtle chemical alterations to the structure of a synthetic monophosphoryl lipid‐A molecule to produce SLA, a designer TLR4 ligand that had a number of desirable adjuvant effects. The SLA molecule stimulated human TLR4 and induced Th1 biasing cytokines and chemokines. On human cells, the activity of SLA plateaued at lower concentrations than the lipid A comparator, and induced cytokine profiles distinct from other known TLR4 agonists, indicating the potential for superior adjuvant performance. SLA was formulated in an oil‐in‐water emulsion, producing an adjuvant that elicited potent Th1‐biased adaptive responses. This was verified using a recombinant Leishmania vaccine antigen, first in mice, then in a clinical study in which the antigen‐specific Th1‐biased responses observed in mice were recapitulated in humans. These results demonstrated that using structure‐based approaches one can predictably design and produce modern adjuvant formulations for safe and effective human vaccines.